Correction to 'Exaggerated trans-membrane charge of ammonium transporters in nutrient-poor marine environments' (2022) by Kellom et al. Issue 9 (28th September 2022) - Kellom, M.; Pagliara, S.; Richards, T. A.; Santoro, A.
Abstract :